Bactericidal effect on Foley catheters obtained by plasma and silver nitrate treatments. (August 2015) - Aflori, Magdalena; Miron, Camelia; Dobromir, Marius; Drobota, Mioara
New medical, materials, and surgical procedures keep improving current health-care practices. Many of these innovations involve polymeric devices that must meet certain clinical and cost requirements. Novel antimicrobial technologies and nanotechnologies are being implemented in more applications such as implant interphases, coatings, and others to avoid postoperatory infections. Here we present a novel approach to create antimicrobial surfaces on Foley catheters widely used in hospitals in order to avoid a variety of harms including infection, pain, and trauma. The combination of plasma and silver nitrate wet treatments demonstrates to be a fast, easy, and convenient method for obtaining colonization-resistant catheter surfaces.